AGENDA SETTING THEORY: SEBUAH TINJAUAN DALAM PERSPEKTIF AKUNTANSI - Mutia, Evi; Evayani, Evayani; Rahmawaty, Rahmawaty; Adnan, Adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
Agenda Setting Theory explains how media influences public attention by determining which issues are perceived as important. Rather than directing what people think, this theory highlights what people think about. In accounting, it provides a useful lens to examine how financial scandals, regulatory developments, sustainability reporting, and transparency are constructed in media narratives. This study aims to explore the application of Agenda Setting Theory in accounting discourse by identifying how media shapes public and institutional responses to accounting-related issues, with a specific focus on under-researched domains such as Islamic accounting and public sector accounting in emerging economies. Using a descriptive analytical approach, this study synthesizes literature to evaluate the role of media in influencing accounting agenda, stakeholder perceptions, and regulatory outcomes. The findings suggest that Agenda Setting Theory is applicable to various branches of accounting, including financial reporting, sustainability disclosures, and standard-setting processes. Media acts as a critical actor in amplifying issues and guiding attention toward specific accounting concerns. However, the study is limited by its reliance on secondary sources. Future research is encouraged to incorporate empirical methods such as interviews or content analysis to deepen the understanding of media's agenda-setting role in accounting contexts.